Relation between Working Periods and Visual Acuity of Welder - Bravery, Amirul Zakiya; Widyaningsih, Vitri; Afifah, Zulaika Nur (Nexus Biomedika, 2015)
Background: Welding process can produce some lights radiation which is dangerous to the welderâs eyes. These lights are visible light radiation, ultraviolet radiation and infrared radiation. These radiations can inflict damage to the eyes especially to the visual acuity of welder. There are some factors that contribute to the damage of welderâs eyes such as working periods . When welders have longer working duration then there will be also a greater risk of dangerous radiation from the welding process. The goal of this study was to know the association between working duration and visual acuity of welding worker. Methods: This study was an analytic observational study with cross-sectional design, which was held on November â December 2014 at Jebres District of Surakarta. Forty six subjects were acquired by exhausted sampling. Subjectâs age was at 19-60 years old and the duration of working was 6-9 hours a day. Working duration data were obtained from interview and visual acuity was measured with optotypes Snellen chart. The data were analyzed using Spearman test for the bivariate analysis and logistic regression for multivariate analysis. Result: This study showed that working periods significantly associated with the visual acuity of welder, due to p-value of Spearman test showed p<0.001 (<0.05) and p-value of logistic regression showed p=0.005 (<0.05). Conclusion: There was an association between working duration and the visual acuity of welder. Welders who had a longer working period had a lower visual acuity Key Words: Welder, Visual Acuity, Working Duration.Â